Second Five Year Plan Nellore District Review of Progress 1956-61 - Planning Commission (Planning Commission, 1956)
Our country has chosen the democratic way to improve the living conditions of the masses inhabiting this sub-continent as against totalitarian methods adopted by some of the countries which have attained Independence in the last two decades. To harness the great mass of humanity with different cultural and linguistic affinities and to lead them towards the path of prosperity and plenty for all, through their voluntary co-operation is a bold venture unheard of, in the annals of history. For this bold experiment the Nation should be grateful to the wise and dynamic leadership of Pandit Jawaharlal Nehru, our beloved Prime Minister.
Planning and Local Administration Department
Planning and Local Administration Department